New measures of monetary policy surprises and jumps in interest rates - León, Ángel; Sebestyén, Szabolcs (Journal of Banking & Finance, 2012)
We propose new surprise measures to characterise two important dimensions of monetary policy. Our measures outperform the traditional monetary shocks in explaining variation of interest rates in the event-study framework. We also study the extent to which the ECB caused jumps in euro area interest rates. The new surprises still prevail upon the traditional ones. Jumps play a great role in the variation of interest rates and the ECB induced several jumps with its decisions, but its predictability has improved over time. We find that, although the surprise measures become somewhat distorted due to money market tensions during the financial turmoil, our model still provides an interesting insight into interest rate behaviour throughout the crisis.